PENGARUH GAYA BELAJAR TERHADAP PRESTASI SISWA DALAM PEMBELAJARAN LITERASI DI UPTD SDN KETETANG 1 KWANYAR - Hasanah, Noviatul; Kusuma, Rendra Sakbana (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This research aims to find out whether there is an influence of learning style on student achievement in literacy learning at UPTD SDN Ketetang 1 Kwanyar. This writing was motivated by the existence of less than optimal student achievement. To respond to this, researchers conducted research on students' learning styles which could influence student achievement. This writing aims to determine learning styles that can be easily accepted by students and improve student achievement in literacy learning at UPTD SDN Ketetang 1 Kwanyar. In this research, case studies were collected using data collection methods. The research was carried out on class 2 students of UPTD SDN 1 Ketetang Kwanyar and the data obtained were primary data and secondary data. The results of this research show an increase in student achievement at UPTD SDN Ketetang 1 Kwanyar. Based on the results of the discussion analysis, it can be seen that learning style greatly influences student achievement in literacy learning, this can be shown by an increase in student scores before and after the research.